(untitled) (Journal of Medical & Health Sciences Review, 2025)
Environmental pollution is one of the most pressing global concerns, primarily driven by rapid urbanization and industrialization. Among various pollutants, mercury (Hg) stands out as one of the most toxic heavy metals, posing serious threats to human, animal, and plant health. This study investigates the potential role of salicylic acid (SA), a plant growth regulator known for its stress-alleviating properties, in mitigating mercury-induced stress in Eruca sativa (arugula), a member of the Brassicaceae family recognized for its nutritional and medicinal benefits. The experiment involved foliar application of salicylic acid at two concentrations (0.5 mM and 2.5 mM) under varying levels of mercury chloride stress (0.5 mM, 1 mM, 2 mM, and 3 mM). Results indicated that mercury stress significantly reduced morphological parameters such as root length, shoot length, leaf length, fresh weight, and dry weight. Additionally, physiological traits including chlorophyll a, chlorophyll b, total chlorophyll, and carotenoid contents were adversely affected. However, the application of salicylic acid ameliorated these negative effects, suggesting its effectiveness in enhancing plant tolerance to heavy metal stress. This study concludes that exogenous salicylic acid application is a promising approach for mitigating mercury toxicity in Eruca sativa.